The Flame Graph. - GREGG, BRENDAN (Communications of the ACM, 2016)
The article discusses the problem of central processing unit (CPU) resource utilization through the "flame" graph during computer programming and program development. Techniques for CPU profiling are compared including stack trace sampling and the use of the programs DTrace and perf_events to optimize application performance of a MySQL database is described.